Using Meteorite Magnetism to Understand the History of Our Solar System: A Decade of Progress and Upcoming Challenges. Issue 3 (17th August 2021) - Nichols, Claire I. O.
Key Points: High spatial and magnetic moment sensitivity microscopy techniques have revolutionized meteorite paleomagnetism in the last decade Fu et al. (2021) used quantum diamond microscopy to reinterpret the magnetization of Allende with implications for the protoplanetary disk Further work is required to interpret extraterrestrial paleomagnetic remanences, and how to recover reliable paleointensity estimates